Disproportionation and self-sorting in molecular encapsulation - Ajami, Dariush (National Academy of Sciences, 2009)
Self-assembled capsules are nanoscale structures made up of multiple synthetic subunits held together by weak intermolecular forces. They act as host structures that can completely surround small molecule guests of the appropriate size, shape and chemical surface. Like their biological counterparts, multimeric enzymes and receptors, the subunits of the capsules are generally identical, and lead to homomeric assemblies of high symmetry. In both biological and synthetic systems small variations in structures are tolerated and lead to heteromeric assemblies with slightly different recognition properties. The synthetic capsules are dynamic, with lifetimes from milliseconds to hours, and allow the direct spectroscopic observation of smaller molecules inside, under ambient conditions at equilibrium in solution. We report here the assembly of hybrid capsules made up of 2 very different structures, both capable of forming their own homomeric capsules through hydrogen bonding. These hybrids exhibit host properties that differ markedly from the parent capsules, and suggest that other capsules may emerge from seemingly unrelated modules that have curved surfaces and are rich in hydrogen bonding capabilities.